DIVERSIFICATION OF FOOD CONSUMPTION BASED ON LOCAL POTENTIAL OF TARAKAN CITY - Galih Yogi Rahajeng; Khotimah Khotimah (Jurnal Borneo Saintek, 2021)
ABSTRACT Diversification of food consumption will provide great benefits if it can explore and develop potential local food sources. However, the diversification of staple food or food sources of carbohydrates which are widely consumed by the people in Tarakan City, still has a single staple food pattern, namely rice. Therefore, a study related to the diversification of non-rice food based on local food needs to be carried out. The specific objectives are to analyze the potential of local food resources in Tarakan City, to analyze food consumption patterns and the level of household food diversification in Tarakan City. ResearchThis technique uses a survey technique with a sample of households in four districts in the City of Tarakan with the sampling technique used is a nonprobability sampling technique with a quota sampling method. The data analysis method used is quantitative descriptive analysis and household dietary diversity score (HDDS). The analysis result shows p Rice production in Tarakan City tends to decline, while the production of cassava and sweet potato shows an increasing trend which indicates the potential for diversification of food production in Tarakan City. Broadly speaking, the pattern of diversification of people's food consumption in Tarakan City is quite diverse based on the amount, quality, and variant, this is shown from the expenditure of various protein sources. However, the diversification of food sources of carbohydrates needs to be studied because of the high expenditure on carbohydrate sources for rice. The level of diversification of food consumption in Tarakan City based on the value of the household food diversity score (HDDS) is in the high category, namely having consumed more than six types of food sources in a day. Keywords: Diversification, Consumption, Food, Household.